Children of Alcoholism the struggle for self and intimacy in adult life - Wood, Barbara L. (New York University Press, 1987)
In this sensitive and richly rewarding book Barbara L. Wood, a clinician with many years' experience working with adult children of the chemically dependent, gives clinicians informed and practical advice on how to treat the damaged self of these individuals. She offers strategies for intervention, along with step-by-step principles that tell the therapist how best to create an environment to help patients